2021
DOI: 10.3389/fnbeh.2021.698516
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate-Induced Changes in Hearing Thresholds in Mongolian Gerbils Are Correlated With Tinnitus Frequency but Not With Tinnitus Strength

Abstract: Tinnitus is an auditory phantom percept without external sound sources. Despite the high prevalence and tinnitus-associated distress of affected patients, the pathophysiology of tinnitus remains largely unknown, making prevention and treatments difficult to develop. In order to elucidate the pathophysiology of tinnitus, animal models are used where tinnitus is induced either permanently by noise trauma or transiently by the application of salicylate. In a model of trauma-induced tinnitus, we have suggested a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…We always combine the results of the GPIAS paradigm with physiological results such as hearing loss, which should be—according to our hypothesis—correlated with the strength of the tinnitus, i.e., the effect size. In a recent publication, we were able to show exactly this correlation [ 31 ], supporting the validity of the method. In line with our animal-experiment tested hypothesis [ 8 , 9 , 20 , 22 , 49 , 50 ], as well as with human patient studies and treatment approaches [ 18 , 19 , 51 ], these animals, therefore, do show behavioral signs of tinnitus.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We always combine the results of the GPIAS paradigm with physiological results such as hearing loss, which should be—according to our hypothesis—correlated with the strength of the tinnitus, i.e., the effect size. In a recent publication, we were able to show exactly this correlation [ 31 ], supporting the validity of the method. In line with our animal-experiment tested hypothesis [ 8 , 9 , 20 , 22 , 49 , 50 ], as well as with human patient studies and treatment approaches [ 18 , 19 , 51 ], these animals, therefore, do show behavioral signs of tinnitus.…”
Section: Discussionsupporting
confidence: 81%
“…The experimenters were blinded to the content of the medium applied (control or EGb 761 ® ). All methods used have been described elsewhere [ 20 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and are, therefore, only briefly described below and schematically depicted in Figure 1 . Briefly, agar medium was applied orally by 15 daily applications, either 3 weeks before or after a mild monaural acoustic noise trauma.…”
Section: Methodsmentioning
confidence: 99%
“…the 5 kHz percept is easier to detect compared to a 2 kHz percept. Additionally, it has already been shown that a GPIAS paradigm is at least partially dependent on cortical learning mechanisms (Moreno-Paublete et al ., 2017; Lanaia et al ., 2021), which may interact (e.g. suppress) the percept after consecutive presentation.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is currently no cure for tinnitus, which is greatly related to the poor understanding of the mechanism underlying tinnitus onset. 5 Salicylate-induced tinnitus model has been widely used for investigating the biological mechanism underlying tinnitus. High doses of salicylate can enhance auditory thresholds, decrease otoacoustic emissions, and reliably trigger tinnitus.…”
Section: Introductionmentioning
confidence: 99%